Expectation to Nuclear Emulsion Technique for New Application in Nuclear Engineering - WATANABE, Kenichi; MORISHIMA, Kunihiro; NAKA, Tatsuhiro; IGUCHI, Tetsuo; KAWARABAYASHI, Jun (Journal of The Society of Photographic Science and Technology of Japan, 2008)
Nuclear emulsion is an excellent three-dimensional position sensitive charged particle detector. We proposed two kind of new applications of this nuclear emulsion to nuclear engineering region. One is a standard detector as a fluence monitor of several keV neutrons. The other is an evaluation of sub-criticality of spent fuel for the purpose of critical safety. Development of the nuclear emulsion in the engineering area will actively be done in near future.